MENINGKATKAN KEMAMPUAN LITERASI YANG BERKARAKTER PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN BAHASA INDONESIA MATERI CERITA BERGAMBAR DENGAN PERMAINAN TREASURE HUNT DAN ORGANIZING THE SEQUENCE KELAS 1 SD N 1 WONOKERSO - Sri Marwati; Siti Rochmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: (1) the implementation of treasure hunt and organizing sequence games in Bahasa Indonesia lesson for the first graders, (2) increasing the literacy skill after the implementation of treasure hunt and organizing sequence games in Bahasa Indonesia lesson for the first graders, (3) students’ responds after following the Bahasa Indonesia lesson with treasure hunt and organizing sequence games. This is a descriptive research with quantitative and qualitative method. the data were collected by observation and questioners. The results of the observation were analyzed quantitatively dan qualitatively, whereas the results of the questioner were analyzed to know the students’ responds predicate toward Bahasa Indonesia lesson with treasure hunt and organizing sequence games. The result of this research is: (1) the implementation had been in accordance with the module with 100% percentage where the teacher had prepared the lesson with games and had been accomplished well, as well as the student could develop the dimension of Pancasila learner profile, (2) there was a significant increase toward the students’ literacy skills, that was 100% of the students got score on range 76-100, (3) the students’ responds towards the implementation of Bahasa Indonesia lesson with treasure hunt and organizing sequence games showed “very like” predicate.